Openness of companies in Serbia to creativity, new ideas and innovation - Miletic, Vuk; Ćurčić, Nikola; Kostić, Zorana (Anali Ekonomskog fakulteta u Subotici, 2021)
The subject of research in this paper is the analysis of openness of companies operating in Serbia to creativity, recognition of new ideas and innovations regardless of size, time period of their operation and the level at which they operate. In conditions of strong competition inovating new categories of products/services is an imperative for the survival of the company, as the number of customers in the world who seek innovation in consumption is growing. The research was conducted based on a specially designed questionnaire on a sample of one hundred and thirty-six companies. The initial assumption is that the inadequate commitment of companies to create innovation causes poor competitiveness in both the national and international markets. The purpose of the research is to evaluate the selected characteristics – the level of openness of the company to entrepreneurship and innovation; identification of the importance of employees in the company as indicators of inventiveness and new ideas; and identifying opportunities and additional initiatives that come from outside the company and are important for the lasting survival of their business in the market. The results of the research show the openness of the company to creativity and new ideas that use the function of permanent survival of the company in the market significantly. In this research, the method of comparative statistics, the hypothetical - deductive method, the analytical-deductive and comparative method, and the historical and statistical - descriptive method were used.